Massa específica e suas implicações na conservação e no valor nutricional em silagens de milho - Krüger, Ana Maria (2012)
The objective of this study was to evaluate new alternative tool for determining the silage density (SD) in corn silage and establish correlations between SD and physical and chemical characteristics of these silages. In the first study there were establishes correlations between the direct method and indirect method to determine the SD of corn silages. SD measurements were done on 14 silos using a metal cylinder attached to a chainsaw. Considering the cylinder volume and weight of the mass removed SD was determined for each silo, measured at five points on the panel. To estimate SD with the indirect method it was used a digital penetrometer, also the points where it was measured the resistance to penetration, were the same perforated with metal cylinder, and in each well was determined two points of resistance, totaling 10 points. It was correlated the values of penetration resistance (MPascal) with the values of SD (kg.m-3) through regression, and then it was estimated the SD. There was a positive relationship between SD of silage and penetration resistance for both natural matter (NM) and for dry matter (DM). Since the fitted equation had a high coefficient of determination, explaining 57% of the variations observed for SDNM and 80% for SDDM, it is concluded that the penetrometer can be used as an indirect method to determine the density of corn silage. In the second study was determined the SD of corn silage in farm conditions, establishing correlations between SD and physical and chemical characteristics of silage, adopting the hypothesis that higher SD can be expressed in better nutritional quality, due to better fermentation pattern. Measures of SD were made in 20 silos with corn silage on dairy farms in the Campos Gerais region (PR), using the metallic cylinder attached to chainsaw similar to the first study. It was found that there were negative relationships between DM and SDNM, ADF and NDF, proving that as higher is DM content it is lower the fiber content in silage, explaining also the wettest materials with more easily compaction. However, the SDNM has a relation with the levels of ADF, NDF, IVDDM and IVDNDF, indicating better quality silage face of higher packing density. The same behavior occurred with SDDM, except for DM, ADF and NDF, deducing that with the lower levels of the fiber plant silage, better packing densities are achieved. As for the ADF and NDF in relation to IVDDM and IVDNDF there was a negative correlation, indicating once again that the lowest participation of fibrous plant indicates better nutritional value and better utilization of nutrients by ruminant animal. It can be concluded that the highest values achieved for SD based both on DM as in the NM express better fermentation conditions reflecting better nutritional value.